2021
DOI: 10.1037/xhp0000907
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the ensemble: Incidental skewing of the perceptual average through memory-driven selection.

Abstract: The process by which multiple items within an object grouping are rapidly summarized along a given visual dimension into a single mean value (i.e., perceptual averaging) has increasingly been shown to interact dynamically with visual working memory (VWM). Commonly, this interaction is studied with respect to the influence of perceptual averaging over VWM, but it is also the case that VWM can support perceptual averaging. Here, we argue that, in the presence of memory-matching elements, VWM exerts an obligatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 85 publications
(164 reference statements)
2
18
1
Order By: Relevance
“…Accordingly, in consideration of this hierarchical structure, matching features through the VWM task would lead to different effects in the highlevel ensemble perception. However, this prediction seems contradict to previous literature in which a similar amplification effect driven by physical saliences was evidenced in both low-level (e.g., orientations of lines; Williams et al, 2021) and high-level (e.g., facial expressions; Goldenberg et al, 2021;Goldenberg et al, 2022;Yang and Baek, 2022) ensemble coding. This suggests that the amplification effect is independent of ensemble perception levels.…”
Section: Introductioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Accordingly, in consideration of this hierarchical structure, matching features through the VWM task would lead to different effects in the highlevel ensemble perception. However, this prediction seems contradict to previous literature in which a similar amplification effect driven by physical saliences was evidenced in both low-level (e.g., orientations of lines; Williams et al, 2021) and high-level (e.g., facial expressions; Goldenberg et al, 2021;Goldenberg et al, 2022;Yang and Baek, 2022) ensemble coding. This suggests that the amplification effect is independent of ensemble perception levels.…”
Section: Introductioncontrasting
confidence: 99%
“…Results of their study showed that the accuracy of the size averaging task was unchanged according to levels of working memory load (i.e., remembering zero, two, or four items), nor was it affected by the VWM task. Considering these findings together, we can conclude that the existence of an inter-task shared feature is crucial for the influence of a memorized item on averaging estimations for a group of properties (Epstein and Emmanouil, 2017;Williams et al, 2021). Overall, these findings aligned well with the amplification hypothesis of perceptual averaging (Kanaya et al, 2018), which stated that physically salient elements are involuntarily and automatically weighted more than less salient elements in the contribution of average estimations (Kanaya et al, 2018;Iakovlev and Utochkin, 2021).…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations